Alexios I Komnenos in the Balkans, 1081–1095 - Meško, Marek. author. aut Link
XVI, 425 p.
Keywords: This book provides a new military history of Byzantine emperor Alexios I Komnenos's campaigns in the Balkans, during the first fourteen years of his rule. While the tactics and manoeuvres Alexios used against Robert Guiscard's Normans are relatively well-known, his strategy in dealing with Pecheneg and Cuman adversaries in the region has received less attention in historical scholarship. This book provides a much-need synthesis of these three closely linked campaigns – often treated as discrete events – revealing a surprising coherence in Alexios' response, and explores the position of Byzantium's army and navy on the eve of the First Crusade. Marek Meško is an assistant professor at the University of Hradec Kralove, Institute of History, Czech Republic. .